Review Pemetaan Domain Pengetahuan Tentang Navigasi Dalam Ruangan Melalui Pendekatan Bibliomatrik - Asep Id Hadiana; Wina Witanti; Agus Komarudin (STMIK IKMI Cirebon, 2021)
Indoor navigation has been recognized as a technological innovation in the field of navigation. Due to the limitations of GPS in indoor areas, indoor navigation has become a growing area of research in recent years. Due to the rapid development of research in the field of indoor navigation, various stakeholders require an up-to-date review of the research and implementation of indoor navigation. The purpose of this study is to provide an objective and accurate summary of the domain in indoor navigation research using 1618 papers related to indoor navigation taken from the SCOPUS database from 2016 to 2021 using bibliometric analysis. The results are useful for identifying clusters and research topics in this community, such as mobile robots, indoor navigation systems, 3d pedestrian indoor navigation and other clusters. More importantly, these results can help highlight how research related to indoor navigation has evolved, thereby greatly contributing to understanding the underlying structure of the field. This study offers useful and new insights to encapsulate the status quo of Indoor Navigation knowledge and can be used as a dynamic platform to integrate the future development of Indoor Navigation